Pemanfaatan Media Infomasi Online Sebagai Strategi Penyuluh Agama Hindu Di Masa Pandemi Covid-19 - A.A. Putra Dwipayana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This paper examines the role of Hindu extension workers who are actually educating and fostering the lives of Hindus by carrying out the extension's productive activities as appropriate. This was taking place during the Covid-19 pandemic that was hitting the world, including in Indonesia. Various government recommendations, both social distancing and physical distancing, require all levels of society to carry out their daily activities at home, and this also has implications for Hindu religious extension workers who take advantage of the role of information technology that is so sophisticated and advanced to sustain activities of the ministry of religion's programs to foster Hindu religious life in particular. So that by utilizing the role of technology and information, it is hoped that it can make the role of extension workers hampered by the outbreak or pandemic of Covid-19. Of course, the continuity to provide and explain the teachings of Hinduism as stated in the religious text